Aging and the Social Ecology of Everyday Interpersonal Perception: What is Perceived, in Whom, and Where?. (10th January 2018) - Castro, Vanessa L; Isaacowitz, Derek M
Abstract: Objectives: Despite a proliferation of research in interpersonal perception and aging, no research has identified the nature of the social and emotional perceptions made by aging individuals in everyday life. In this study, we aimed to identify the social ecological features that characterize everyday interpersonal perception across the adult lifespan. Method: Three studies were conducted. Study 1 identified and compared the targets and locations of young, middle-age, and older adults' everyday interpersonal perceptions; these perceptions were categorized into types in Study 2. Study 3 applied these categorizations to identify and compare the social ecology surrounding aging individuals ' interpersonal perceptions. Results: Everyday interpersonal perceptions were directed toward familiar others and occurred in familiar locations, although the specific familiar targets and locations sometimes varied significantly with age. However, the types of perceptions made in everyday life did not vary significantly between age groups. Discussion: Aging individuals make similar types of interpersonal judgments, but the targets and locations of these judgments may change with age. Future studies on interpersonal perception and aging will need to account for these features of the aging individual ' s social ecology to provide an accurate assessment of the aging process.